Penerapan Nilai-Nilai Agama dan Moral Pada Anak Usia 5-6 Tahun di Taman Kanak-Kanak Al Ijtihad Samarinda - Ardiana, Reni; Aslindah, Andi (PT Literasi Nusantara Publisher, 2023)
The definition of early childhood (AUD) in general is children aged 0 to 6 years included in the golden period, so children aged 4-6 years are a critical period for children, because during this period the process of maturity of physical and psychological functions that are ready to respond to circumstances and environmental stimulation in children. This period is the beginning of the development of physical motor, cognitive, language, social, emotional, independence, art, religious and moral values of children. Therefore, we need a condition that can provide encouragement according to the needs of children, so that the growth and development of children is achieved optimally (Ministry of National Education, 2010). Early childhood education (PAUD) is the best and most appropriate period in laying the foundations of religious and moral values. One of the basic attitudes that must be possessed by children to become good and true human beings is to have good attitudes and moral values, both in the family and in the community. Although the role of parents is very large in building the moral and religious basis for their children, the role of Early Childhood Education educators is also not small in laying down the basic moral and religious values for a child (Hidayat, 2007:38).